Homeodomain-leucine zipper proteins interact with a plant homologue of the transcriptional coactivator multiprotein bridging factor 1 - Zanetti, María Eugenia (2004)
StMStMBF1 (Solanum tuberosum multiprotein bridging factor 1) is a plant member of the MBF1 family of transcriptional co-activators. In an attempt to understand the role of StMBF1, we analyzed its interaction with plant transcription factors of the homeodomain-leucine zipper (Hd-Zip) family, a group of proteins with a typical leucine zipper motif adjacent to a homeodomain. StMBF1 is able to interact in vitro with the Hd-Zip protein Hahb-4 both in the presence and absence of DNA. Upon binding, StMBF1 increases the DNA binding affinity of Hahb-4, and of another plant homeodomain containing protein from the GL2/Hd-Zip IV family, HAHR-1. The biological role of interactions is discussed in this paper.